Phytogenic Feed Additives in Ruminant Nutrition: Rumen Modulation, Performance, and Sustainability – A Review (Tikrit Journal of Veterinary Science, 2025)
In order to satisfy consumer demands for natural and sustainable products, the livestock industry must adapt to stricter laws governing the use of antibiotic growth promoters (AGP). Phytogenic feed additives (PFAs) have drawn a lot of interest in this context as a substitute to enhance ruminant performance. Essential oils, polyphenols, saponins, tannins, and other plant-derived substances are all included in the large class of compounds known as PFAs. These substances include a wide variety of bioactive compounds that have intricate and multifaceted effects on the performance and health of ruminants. An overview of the state of knowledge regarding the application of PFAs in ruminant production is given in this review. It encapsulates their primary modes of action, which include host metabolism, digestive enzyme activity, and rumen microbiota modulation. The review specifically addresses PFAs' ability to alter rumen fermentation in a way that enhances volatile fatty acid (VFA) production, lowers ammonia concentration, and—above all—decreases enteric methane production. Examined are the ensuing impacts on productive performance. Because of their immunomodulatory, anti-inflammatory, and antioxidant qualities, which can lessen stress and increase resistance to disease, PFAs may also contribute to the advancement of animal welfare. The study also discusses some of the drawbacks of using PFAs, including response variability based on the plant source, extraction technique, dosage, and diet. This emphasizes how production and use of PFAs require standardization and quality control. This review paper concludes by summarizing the body of research on PFAs' use in ruminant production, including information on their mode of action, performance effects, possible health advantages, and environmental effects. Designing more sustainable and effective ruminant production systems that satisfy consumer demands and legal requirements is possible with the knowledge provided in this paper.